GIST Strategy Effect on Reading Descriptive Text - Kusmaning Ayu Dewi Renjani; Ermawati Z Nuroh (International Consortium of Education and Culture Research Studies, 2021)
The purpose of this study to find out whether there is a significant effect of GIST strategy to teach reading comprehension in descriptive text of seven grade students. This study uses quantitative method. The study usedtrue experimental which took two classes randomly, VII I as experimental class and VII H as control class. The instrument used a test. The result showed from a mean of the pretest in experimental class is 75.13 and posttest is 86.94. The researchers used the ttest formula to calculate the results of the data and hypothesis. The result of tvalue is higher than a ttable,ttest is 3.415 higher than ttable 1.994 with degree freedom 70 and level significance 5%. It means that the Ha is accepted and H0is rejected. The concluded there is a significant effect of GIST strategy to teach reading comprehension of seven grade students at SMPN 4 Sidoarjo.